CPA Examination: Theory of Accounts. - Zlatkovich, Charles T. (The Accounting Review, 1965)
Abstract The article presents the theory of accounts portion of the Uniform Certified Public Accountants Examination held in November 1964. In one of the questions, the students had to identify and discuss defects in the given financial statements with respect to terminology, disclosure and classification. The answer of one of the students discussed the term "reserve for doubtful accounts" which is no longer regarded as desirable. The term "reserve," where used at all, should be employed in connection with appropriations of retained earnings. The student wrote that combining sales and interest income to arrive at total revenue is acceptable where the single-step form of income statement presentation has been adopted; the remainder of the statement fails to follow this form and it would therefore be preferable to set out only the major revenue source at the top of the statement. Another questions asked to discuss the theoretical justification of the allowance method as contrasted with the direct write-off method of accounting for bad debts.